Cumulative Advantage in the Skill Development of STEM Graduate Students: A Mixed-Methods Study. (February 2016) - Feldon, David F.; Maher, Michelle A.; Roksa, Josipa; Peugh, James
Studies of skill development often describe a process of cumulative advantage, in which small differences in initial skill compound over time, leading to increasing skill gaps between those with an initial advantage and those without. We offer evidence of a similar phenomenon accounting for differential patterns of research skill development in graduate students over an academic year and explore differences in socialization that accompany diverging developmental trajectories. As predicted, quantitative analysis indicated large effect sizes for skill gains after controlling for initial performance levels. Qualitative analyses indicated that students with initial advantages were more likely to report greater demands of independence by their advisors and see more extensive value in research tasks comparable to those assigned their less skilled peers.